(untitled) (The Review of Diabetic Studies, 2024)
One area of medicine where nanobiotechnology is having a positive impact in a number of ways is dentistry. This review’s goal is to educate readers on the many applications of the nano-dental complex, or nano dentistry, in healthcare and how emerging technologies are transforming the dental industry. A methodical strategy was used to gather the most recent information on dentistry and nanotechnology from sources such as Scopus, Google Scholar, PubMed, and official websites like the WHO. Using nanomaterials, nanorobots, and nanotechnology to identify, treat, and prevent dental conditions is known as "nano dentistry," and it is a rapidly developing area of dentistry. This present study will assess the development in the said area of dentistry and the sources of data will be secondary in nature. The time frame of the study will 2015 to 2023.